2007
DOI: 10.1016/j.mar.2006.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Sourcing of internal auditing: An empirical study

Abstract: In recent years, the scope of internal auditing has broadened considerably, increasing the importance of internal auditing as part of the organization's management control structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
2
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 27 publications
3
43
2
1
Order By: Relevance
“…In other words, SMEs are not capable to generate economies of scale for the non-routine management accounting practices that are recurrent and sizeable, in order that they are less likely to provide such accounting functions inside the firm. Hence, our finding contradict with previous study (Everaert et al, 2010;Kamyabi & Devi, 2011e;Spekle´ et al, 2007;Widener & Selto 1999;Williamson, 1985) which indicated frequency was statistically and negatively related to outsourcing of routine and non-routine accounting tasks.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In other words, SMEs are not capable to generate economies of scale for the non-routine management accounting practices that are recurrent and sizeable, in order that they are less likely to provide such accounting functions inside the firm. Hence, our finding contradict with previous study (Everaert et al, 2010;Kamyabi & Devi, 2011e;Spekle´ et al, 2007;Widener & Selto 1999;Williamson, 1985) which indicated frequency was statistically and negatively related to outsourcing of routine and non-routine accounting tasks.…”
Section: Discussioncontrasting
confidence: 99%
“…The decision to outsource or internalize depends on the comparative transaction cost to avail that service such as the ex-ante negotiation cost and the ex-post performance and feedback (Williamson, 1985). TCE describes frequency, asset specificity and trust in accountant are essential components influencing accounting outsourcing decision (Everaert et al, 2010;Lammirmiaki, 2005;Spekle et al, 2007). Resource based view (RBV) theory has happened to a practical framework to describe why SMEs use external accountant services under competitive pressure (Gooderham et al, 2004).…”
Section: Theoretical Framework and Hypothesismentioning
confidence: 99%
“…These categories lack strategic sourcing methodology, environmental services, mailing/distribution, legal services, external manufacturing and infrastructure maintenance. Speklé et al (2007) consider the internal audit sourcing decisions of 66 Dutch companies, and find that where larger firms seek to have an internal auditing department, smaller firms look to the external supply. Furthermore, companies integrate or establish an internal function if company-specific knowledge and intensive collaboration with the management is required.…”
Section: Products and Service Sourcingmentioning
confidence: 99%
“…However, buyers tend to have a long-term sourcing focus (Cox et al, 2005;Speklé et al, 2007) and have to deal with a complex field in services orders. Selviaridis et al (2011) discuss the complexity of services sourcing and changed orders caused by supplier de-pendence or weak capabilities in sourcing.…”
Section: Products and Service Sourcingmentioning
confidence: 99%
See 1 more Smart Citation